2012
DOI: 10.1186/1478-7954-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in Tonga: quality of certification and implications for statistics

Abstract: BackgroundDetailed cause of death data by age group and sex are critical to identify key public health issues and target interventions appropriately. In this study the quality of local routinely collected cause of death data from medical certification is reviewed, and a cause of death profile for Tonga based on amended data is presented.MethodsMedical certificates of death for all deaths in Tonga for 2001 to 2008 and medical records for all deaths in the main island Tongatapu for 2008 were sought from the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
(13 reference statements)
1
21
0
Order By: Relevance
“…Unfortunately, even in countries where hospital data are the only source of cause-of-death information, data quality is rarely evaluated. Research in different countries has repeatedly identified substantial misclassification of the cause of death of people who die in hospitals – with attendant implications for the use of cause-of-death data in informing policy 14 20 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, even in countries where hospital data are the only source of cause-of-death information, data quality is rarely evaluated. Research in different countries has repeatedly identified substantial misclassification of the cause of death of people who die in hospitals – with attendant implications for the use of cause-of-death data in informing policy 14 20 …”
Section: Introductionmentioning
confidence: 99%
“…While the high proportion of NCDs in adults from the health facility data may in part be attributed to reporting of non-specific causes such as "heart problem" and "heart-stopped", that this pattern is reflected in the hospital separation and medical certificate data adds to the evidence that mortality burden from NCDs is significant. The high proportion of deaths attributed to NCDs such as cardiovascular disease and diabetes in adults aged 15-59 is consistent with patterns seen in other PICTs (such as Fiji, Nauru and Tonga (93,112,347)), where NCDs have contributed to high premature adult mortality and subsequently limited improvements in LE.…”
Section: As Vanuatu Continues To Improve Data Collection and Further supporting
confidence: 79%
“…al. (2) were derived from demographic analysis of the most recent census; both of which were based on model life tables derived from a single 335 parameter input (child survival) in the absence of any better data sources; and as such are most likely to be based on an under-estimation of adult mortality (93,112,347).…”
Section: Summary Measures Of Mortalitymentioning
confidence: 99%
“…Diagnostic uncertainty is commonly encountered by health care providers in sub-Saharan Africa given the limited access to resources needed to evaluate patients. Research from several countries (South Africa [21], Mexico [22], China [23] and Tonga [24]) has identified substantial misclassification of in-hospital causes of death. While it is wellknown that lacking a diagnosis leads to delay in appropriate care and subsequently increases the risk of death [25,26], we are not familiar with other studies conducted within sub-Saharan Africa which report both the rate of unknown diagnoses during hospitalization and its influence on mortality.…”
Section: Discussionmentioning
confidence: 99%